Synthesis of Organofluoro Compounds Using Methyl Perfluoroalk‐2‐ynoates as Building Blocks. Issue 2 (10th March 2016) - Sun, Xuechun; Han, Jing; Chen, Jie; Zhang, Hui; Cao, Weiguo
Abstract: This review provides an overview of several synthetic applications of methyl perfluoroalk‐2‐ynoates, leading to convenient preparation of many perfluoroalkylated compounds. The use of these important substrates in the synthesis of various five‐, six‐, and seven‐membered heterocycles, cyclopentadienes, and biphenyls is described, alongside a discussion of the mechanistic aspects of these reactions. Abstract : Synthetic applications of methyl perfluoroalk‐2‐ynoates, leading to the convenient preparation of a wide range of perfluoroalkylated compounds, are reviewed.